Preparation of Metal–Organic Frameworks UiO-66 for Adsorptive Removal of Methotrexate from Aqueous Solution - Aghajanzadeh, Mozhgan; Zamani, Mostafa; Molavi, Hossein; Khieri Manjili, Hamidreza; Danafar, Hossein; Shojaei, Akbar (Journal of inorganic and organometallic polymers and materials, 2018)
A low cytotoxic metal–organic framework (MOF) UiO-66 (UiO stands for University of Oslo) and NH 2 -UiO-66, that showed high cell viability of HFF-2 via 3-(4, 5-dimethylthiazol-2-yl) 2, 5-diphenyl tetrazolium assay, was reported as an effective adsorbent (antidotal) agents. The structure of MOFs was confirmed by Fourier transform infrared, Field emission scanning electron microscopy (FESEM) and X-ray diffraction. Thermal behavior of MOFs was investigated using with thermogravimetric analyzer in nitrogen atmosphere to check the thermal stability. FESEM showed NH 2 -UiO-66 displayed symmetrical crystals with triangular base pyramid morphology, with the particle size around 100 nm and uniform size distribution. The specific surface areas were calculated using the Brunauer–Emmett–Teller method and surface area and total pore volume of NH 2 -UiO-66 were calculated to be 1258 m 2 /g and 0.51 cm 3 /g, respectively. Methotrexate salt (MTX) was selected as the model drug which was adsorbed into inner pores and channels of MOFs by diffusion manner. The interaction between MOFs and MTX and the effect of pH on interaction between them in aqueous solution was investigated. The final results showed that UiO-66 have high adsorbing capacity and great affinity to MTX.